On properties of n-totally projective abelian p -groups - Danchev, P. V.; Keef, P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove some properties of n-totally projective abelian p-groups. Under some additional conditions for the group structure, we obtain an equivalence between the notions of n-total projectivity and strong n-total projectivity. We also show that n-totally projective A-groups are isomorphic if they have isometric p^n-socles.